2005
DOI: 10.1186/1471-2350-6-17
|View full text |Cite
|
Sign up to set email alerts
|

The Familial Intracranial Aneurysm (FIA) study protocol

Abstract: Background: Subarachnoid hemorrhage (SAH) due to ruptured intracranial aneurysms (IAs) occurs in about 20,000 people per year in the U.S. annually and nearly half of the affected persons are dead within the first 30 days. Survivors of ruptured IAs are often left with substantial disability. Thus, primary prevention of aneurysm formation and rupture is of paramount importance. Prior studies indicate that genetic factors are important in the formation and rupture of IAs. The longterm goal of the Familial Intracr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 54 publications
(30 reference statements)
0
45
0
2
Order By: Relevance
“…Most of the aneurysms were small: 2 IAs were ≥7 mm in maximal diameter; 19 were 4-6 mm; and 50 were 2-3 mm. Aneurysms arose most commonly on the ICA, with 31 such lesions (8 OphA, and 23 other ICA), followed in frequency by the MCA (20), PCoA (8), anterior cerebral artery (7), ACoA (3), and other locations (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the aneurysms were small: 2 IAs were ≥7 mm in maximal diameter; 19 were 4-6 mm; and 50 were 2-3 mm. Aneurysms arose most commonly on the ICA, with 31 such lesions (8 OphA, and 23 other ICA), followed in frequency by the MCA (20), PCoA (8), anterior cerebral artery (7), ACoA (3), and other locations (2).…”
Section: Resultsmentioning
confidence: 99%
“…2 The study was approved by the institutional review board/ethics committee at each of the study centers and recruitment sites.…”
Section: Clinical Materials and Methodsmentioning
confidence: 99%
“…[3][4][5] Furthermore, several studies suggested an increased occurrence of IA and SAH in first-and second-degree relatives of SAH, with the incidence rate of 6-10%. [6][7][8][9] Several Mendelian disorders, such as autosomal-dominant polycystic kidney disease and Ehlers-Danlos syndrome type IV are associated with an increased risk of IA formation. 10,11 All these evidence fortified the roles of genetic factors in the pathogenesis of IA.…”
Section: Introductionmentioning
confidence: 99%
“…The investigators' first goal will be to carry out a 10-cM genome screen to identify familial IA susceptibility loci (Broderick et al 2005). With a sample size of this magnitude, many further studies could lead to meaningful results.…”
Section: Chromosomal Loci Mapped By Linkage Studiesmentioning
confidence: 99%